Pancreaticoduodenectomy with right hemicolectomy for advanced malignancy: a single UK hepatopancreaticobiliary centre experience. (1st September 2022) - Das, Bibek; Fehervari, Matyas; Hamrang‐Yousefi, Sahar; Jiao, Long R.; Pai, Madhava; Jenkins, John T.; Spalding, Duncan R. C.
Abstract: Aim: Locally advanced intestinal neoplasms including colon cancer may require radical en bloc pancreaticoduodenectomy and right hemicolectomy (PD‐RC) to achieve curative, margin‐negative resection, but the safety and benefit of this uncommon procedure has not been established. The Association of Coloproctology of Great Britain and Ireland IMPACT initiative has also highlighted a lack of awareness about current services available within the UK for patients with advanced colorectal cancer and concerns about low‐volume centres managing complex cases. Thus, we aimed to review the feasibility, safety and long‐term outcomes of this procedure at a single high‐volume hepatopancreaticobiliary surgery unit in the UK. Method: A retrospective cohort study was performed using a database of all consecutive patients with intestinal cancer who had been referred to our regional advanced multidisciplinary team and undergone PD‐RC in a 7‐year period (2013–2020). Clinico‐pathological and outcome data were reviewed. Results: Ten patients (mean age 54 ± 13,  8/10 men) were identified. Final histology revealed the primary tumour sites were colon ( n  = 7) and duodenum ( n  = 3). R0 resection was achieved in all cases. The major complication rate (Clavien–Dindo ≥ 3) was 10% (1/10) with no deaths within 90 days of surgery. The Kaplan–Meier estimated 5‐year overall survival was 83.3% (95% CI 58.3%–100%). Univariate survival analysis identified perineural invasion and extra‐colonic origin as predictors of poor survival (log‐rank P  < 0.05). Conclusion: En bloc PD‐RC for locally advanced intestinal cancer can be performed safely with a high proportion of margin‐negative resections and resultant long‐term survival in carefully selected patients.